SISTEM AGEN CERDAS BERBASIS WEB UNTUK KOMPUTASI INFORMASI KINERJA DARI PELAKSANAAN PROYEK-PROYEK PERUSAHAAN - Azhari Subanar; Retantyo Wardoyo; Sri Hartati (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2010)
In this paper are presented the development of a model of intelligent software agents to support web-based computing of project performance information that being executed by the company. The project performance is calculated by using earned value management method. We have developed a prototype of the intelligent agent software based on Jadex agent framework. Based on some simple data simulations of enterprise projects, our agents have showed capabilities in calculating the performance value of projects and displaying into barchart or S-graph.